Disproportionate mitral regurgitation: new entity or reflection of measurment errors?. (8th February 2021) - Ambrozic, J; Rauber, M; Skofic, N; Toplisek, J; Berlot, B; Bervar, M; Cvijic, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The results of recent studies of transcatheter mitral valve repair proposed a new conceptual framework that categorized mitral regurgitation (MR) into proportionate (propMR) or disproportionate (dispropMR) according to the relationship between effective regurgitant orifice area (EROA) and left ventricular (LV) end-diastolic volume (EDV). Purpose: To determine the prevalence of dispropMR in consecutive heart failure patients with reduced ejection fraction (HFrEF) undergoing clinically indicated echocardiography over one year period and to examine characteristics of this new entity. Methods: We retrospectively identified 179 patients(age:69 ± 12 years, male:132[74%]) with HFrEF who were classified more than mild MR by performing echocardiographer. Following parameters of MR severity were analysed: regurgitant volume(PISA-based regurgitant volume[RVol-PISA] and RVol calculated by the difference of total LV stroke volume by LV planimetry and Doppler-estimated effective LV stroke volume[RVol-SV]), PISA-based EROA and regurgitant fraction (RF). Grading of MR severity based on RVol was performed (mild:<30 ml, mild-moderate:30-44ml, moderate-severe:45-59 ml, severe:≥60 ml). The distinction between propMR and dispropMR was determined by using a proportionality scheme by Grayburn, considering ratio EROA/LVEDV. DispropMR was identified by the ratio greater than 0.14, while the others were classified as propMR. Results: In our cohort, 49(27.4%)patients had dispropMR. Both MR groups were comparable in age and gender. DispropMR group had significantly smaller LV dimensions(LV end-diastolic diameter:59 ± 9mm vs. 65 ± 8mm, p < 0.001; LVEDV:164 ± 54ml vs. 222 ± 60ml, p < 0.001) and higher EF(41 ± 11% vs. 34 ± 9%, p < 0.001). Higher proportion of primary MR was noted in dispropMR group(15[31%] vs. 4[3.3%] patients, p < 0.001). Significant differences were observed in PISA-based quantification of MR between both groups (p < 0.001, for all), whereas RVol-SV was comparable(p = 0.667;Figure A). Discrepant grading in MR severity between RVol-PISA and RVol-SV methods was observed(p < 0.001), with significant high discordance in dispropMR(p < 0.001) and no significant differences in propMR(p = 0.187;Figure B). Additionally, difference in RVol assessed by PISA method and SV method were more prominent in dispropMR (RVol difference: dispropMR:27 ml[17-46] vs. propMR:13 ml[-4 to 24], p < 0.001). MR severity would be reclassified in a substantial proportion of dispropMR when considering RVol-SV. Conclusion: Our results suggest that dispropMR may be found in roughly one fourth of echocardiographic studies in patients with HFrEF. DispropMR patients have less extensive LV remodelling and more severe MR based on PISA parameters compared to propMR. However, inconsistencies between parameters of MR severity in dispropMR might suggest echocardiographic limitations of quantitative grading of the MR severity or/and LV volume assessment rather than a new pathophysiological concept of disproportionate MR.